Case report of pseudomembranous colitis in a 3-year-old resulting from Clostridium difficile infection not associated with prior antibiotic therapy - Akram, Lubana; Mazumder, Md Wahiduzzaman; Begum, Fahmida; Musabbir, Nadira; Hassan, Md Nazmul (Indonesian Pediatric Society, 2024)
Pseudomembranous colitis (PMC) is a serious condition caused by Clostridium difficile, frequently arising after antimicrobial therapy. In recent years, Clostridium difficile infection rates have been rising and more younger patients have been affected than adult. This case report is about a 3-year-oldboy with clinical, laboratory, and endoscopic findings typical of pseudomembranous colitis, without a history of previous antibiotic therapy.